Machine Learning and Artificial Intelligence as Educational Games - Po Abas Sunarya (Pandawan Sejahtera Indonesia, 2022)
Digital games are establishing themselves as a new paradigm in teaching. Everyone can play digital games, they're economical, and they're a terrific way to learn. Digital games that encourage computational thinking and programming have recently attracted more attention in pre-college (K–12) educational institutions. A growing number of students have been drawn to the subjects of In recent years, there has been an increase in artificial intelligence (AI) and machine learning (ML). Researchers in teaching and learning are interested in the integration of AI/ML with digital gaming, however there hasn't been a literature review in this field. This paper aims to summarize the most recent findings on instructional video games for AI and ML. A qualitative content analysis was conducted using the relevant essays and games that were selected following a comprehensive search. Using this summary as a base, we present a list of research publications and games that are relevant. illustrating the unique opportunities that diverse games offer to teach various AI and ML techniques and topics.